Circuit breakers: A survey among international trading venues - Benjamin Clapham; Peter Gomber; Martin Haferkorn; Paul Jentsch; Sven Panz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
Circuit Breakers are widely implemented in 2016. Currently, the majority (86%) of the responding trading venues use circuit breakers to ensure investor protection and to increase market integrity and stability. Compared to the previous study (WFE, 2008), the proportion of exchanges using circuit breakers increased from 60% to 86%. The most widely-used circuit breaker mechanisms are market-wide trading halts and volatility interruptions. On cash markets, market-wide trading halts and volatility interruptions represent 72% of the implementations. On derivatives markets, most exchanges coordinate their circuit breaker with their cash market (40%) followed by market-wide trading halts (20%) and volatility interruptions (13%). The majority of mechanisms do not differentiate between upward or downward market movements. Either way, when price fluctuations are extensive, circuit breakers are triggered. In the cash market segment, only 15 of 47 (32%) mechanisms react solely to downward market movements. Thirteen of 15 (87%) circuit breakers on the derivatives markets are triggered in both directions. Only in two cases of internal coordination between cash and derivatives markets, the respective trading halt on both market segments is only triggered in the event of down-ward market movements. Most circuit breakers are triggered by predetermined price ranges that are either static or dynamic with the former being set wider than the latter. It is noticeable that only volatility interruption mechanisms apply dynamic price ranges (in most cases in combination with static ranges). The other three types of circuit breakers rely on static price ranges, which typically refer to the previous days closing prices or last auction prices. Transparency dominates when it comes to providing information on the thresholds to market participants. The vast majority (92%) of responding exchanges publishes all information regarding the threshold determination process and the thresholds themselves. However, three exchanges only provide general information, but do not disclose specific parameters such as the width of price ranges to avoid deliberate triggering of the circuit breaker. There is support for greater coordination of circuit breakers across venues. The study gathered a multitude of opinions of global trading venues and thus serves as further input to this important topic. Although 20 of 29 responding exchanges (69%) generally favor the concept of coordination, only 32% of the exchanges that make use of circuit breakers already co-ordinate them with other venues.
urn:nbn:de:hebis:30:3-457679
Keywords: 330